Structural modification and conductivity enhancement of NiCl2 incorporated P3HT: PC60BM based organic photoactive layer - Tan, Sin Tee; Hong, Kai Jeat; Hilm Rizal, Nur Elmira Melissa; Lau, Kam Sheng; Yap, Chi Chin; Chia, Chin Hua; Chong, Kok-Keong (Elsevier, 2023)
The poor crystalline structure in P3HT has limited the device performance of organic photovoltaic. Surface modification of P3HT has been reported to enhance the intrinsic properties of the molecular structure. This project focus on the incorporation of NiCl2 at different volume percentages into P3HT: PC60BM active material. The structural, electrical, and optical properties of the active material after the metal halide modification is elucidated. The result showed that the 20 vol% of NiCl2 sample present 45% increment in its electrical conductivity and 37% in the photoabsorbance ability. The presence of NiCl2 can served as a surface passivation to reduce the moisture level in P3HT which indirectly improve the surface activity of P3HT based active material. This novel finding can serve as an alternative to improve the device performance of P3HT based active material in organic solar cell fabrication.